Modified Keystone Flap: A Versatile Reconstruction for Mastectomy Defects – Our Clinical Experience - Anastasia Dessy Harsono; Dominic Melino Tjokrovonco (The ASEAN Journal of Military and Preventive Medicine, 2024)
Introduction: The closure of extensive defects in reconstructive surgery is a common challenge. The keystone flap technique has gained popularity due to its adaptability and reliance on fascia, providing a reliable blood supply and offering a better match for skin color compared to skin grafts. However, keystone flap necrosis can occur due to tension and inadequate tissue perfusion. To address this, a modified keystone flap technique called the "doubled-handle saucepan" was developed, resulting in improved flap vitality and reduced tissue necrosis, particularly in mastectomy defects. Materials and method: We assessed 16 female patients who underwent “doubled-handle saucepan” keystone flaps after modified radical mastectomy (MRM). The average dimensions of wounds in this study were 23.1 ± 3.8 cm × 16.9 ± 2.9 cm, with the largest defect measuring 28.0 cm × 21.5 cm. The average size of the modified keystone flap was 36.3 ± 3.8 cm × 21.2 ± 2.2 cm. Results and Discussion: Modified keystone flap demonstrated effective performance in managing extensive defects without any complication. The average operation time in our study was 124.3 ± 11.2 minutes. Conclusion: The "double-handled saucepan" keystone flap technique is a unique and dependable method derived from the original keystone flap which effectively covers defects and maintains flap vitality without tension by ensuring vascularization at the skin bridge. This modified keystone flap technique proves highly effective for reconstruction after modified radical mastectomy (MRM), offering time efficiency and no need for a secondary donor site makes it an appealing alternative to free flaps or other local flap techniques in many cases.